Genetic heterogeneity of chicken anemia virus isolated in selected Egyptian provinces as a preliminary investigation - Abdel-Mawgod, Sara; Zanaty, Ali; Elhusseiny, Mohamed; Said, Dalia; Samir, Abdelhafez; Elsayed, Moataz M.; Mahana, Osama; Said, Mahmoud; Hussein, Ahmed M.; Hassan, Heba M.; Selim, Abdullah; Shahien, Momtaz A.; et al. (Frontiers in Veterinary Science, 2024)
Chicken anemia virus (CAV) is a widespread and economically significant pathogen in the poultry industry. In this study 110 samples were collected from various poultry farms in selected Egyptian provinces during 2021–2022 and were tested against CAV by Polymerase Chain Reaction (PCR), revealing 22 positive samples with 20% incidence rate. Full sequence analysis of five selected CAV strains revealed genetic variations in VP1, VP2, and VP3 genes. Phylogenetic analysis grouped the Egyptian strains with reference viruses, mainly in group II, while vaccines like Del-Rose were categorized in group III. Recombination events were detected between an Egyptian strain (genotype II) and the Del-Rose vaccine strain (genotype III), indicating potential recombination between live vaccine strains and field isolates. To evaluate pathogenicity, one Egyptian isolate (F883-2022 CAV) and Del-Rose vaccine were tested in Specific Pathogen Free (SPF) chicks. Chicks in the positive group displayed clinical symptoms, including weakness and stunted growth, with postmortem findings consistent with CAV infection. The vaccine group showed milder symptoms and less severe postmortem changes. This study provides important insights into the genetic diversity of CAV in selected Egyptian poultry farms showing recombination event between field strain and vaccine strains, highlighting the need for advanced vaccination programs, especially for broilers.